Abses Bezold Et Causa Mastoiditis Akut Dextra Dengan OMA Stadium Oklusi Pada Pasien DM - Zikral Hadi; Aiman Kamila (Journal Innovation In Education, 2023)
Introduction : Mastoiditis is inflammation that occurs in the mastoid bone located in the temporal bone. Mastoiditis can affect all ages, both children and adults. The most frequent cause of the disease is stressptococcus pneumonia. This disease requires surgery as soon as possible. Mastoiditis can develop into a bezold abscess if left untreated. Case report: This case report is about a 31-year-old male patient complaining of swelling the size of a marble seed on the bone behind the right ear ± 1 week, swelling from the protruding bone behind the right ear to the neck. Swelling is accompanied by pain, redness, fluctuations (+), fever that disappears and decreased hearing function. Conclusion: The patient has a bezold abscess preceded by mastoiditis. The diagnosis in this patient is based on history, physical examination, and supporting examinations in the form of laboratory and mastoid X-rays with stenvers and schuller positions. In patients carried out drainage measures of abscesses as well as pharmacotherapy administration.